Spinal Anesthesia for Laparoscopic Cholecystectomy - Luiz Eduardo Imbelloni (Global Journal of Anesthesiology - Peertechz Publications, 2014)
In 1985, the first laparoscopic cholecystectomy was performed, and the introduction of laparoscopic cholecystectomy proved to be a new era in the management of cholelithiasis. In his only start, only patients who were good surgical risks, with non acute disease and no prior abdominal surgeries were selected for the procedure. However, as experience was gained, the pool of patients expanded to encompass those who were otherwise candidates for conventional cholecystectomy. To perform the surgery laparoscopically, there is a need to create a space between the abdominal wall and the viscera. If cholecystectomy was performed under anesthesia in high-risk patients, there is no explanation for the procedure to become routine in healthy patients. Spinal anesthesia has the advantage of providing analgesia and muscle relaxation with complete preservation of consciousness and rapid postoperative recovery. No need to change the surgical technique, only that the inflation pressure should be maintained between 8 and 10 mmHg. One of the problems is the appearance of shoulder pain, which can be seamlessly decreased with low intraabdominal pressures and systematic use of intraperitoneal local anesthetics. Spinal anesthesia reduces the incidence of nausea and vomiting and improves postoperative pain and allows early ambulation and discharge.The cost of spinal anesthesia was 30% of general anesthesia.